Pengaruh limbah logam pada kuat tekan beton - Setiawati, Dewi; Jatmika, Bambang; Aditya, Muhammad Rizal (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2021)
This study aims to determine the effects of nickel slag in the concrete mixture and on its compressive strength value. In this study, cylindrical specimen having 15cm diameter and 30cm height is used. We have used nickel slag as substitute of coarse aggregate in weight ratio of 25%, 50% & 100% respectively of coarse aggregate in sample. The ratio of concrete mixture used in this study is comprised of ratio 1:2:3 of cement, sand & gravel respectively. Compressive strength was used as a parameter for testing the samples in this study. Test was performed using compression Testing machine, from the test results, the mean value of the average compressive strength of cylindrical concrete at the age of 3 days with a 25% variant nickel slag is 134.02 kg / cm2, 50% variant nickel slag is 165.76 kg / cm2, and 70% variant nickel slag is 148.92 kg / cm2, at age 7 days for the 25% is 219.61 kg / cm2, the 50% variant is 191.27 kg / cm2, and the 70% is 181.57 kg / cm2, while at the age of 28 days the 25% is 275.09 kg / cm2, the 50% iis equal to 296.28 kg / cm2, and the 70% is 225.37kg / cm2